The “Playful Paradigm”. A Smart Transformation for the Contemporary Society? - Iannuzzi, Ilaria (SocietàMutamentoPolitica, 2023)
This article aims to offer a critical examination of the current gamification process existing in contemporary society. One example of this process is the “Playful Paradigm”, a European-level project aiming to help cities – considered increasingly smart – to develop pragmatic solutions that are new and sustainable and that integrate urban economic, social and environmental topics. What critical issues hide behind prevailing gamification? In terms of general theorisation, discussion will be hinged on the conceptual category of the “homo ludens” and, more generally, the “casino culture”, so as to thrown new light, through a sociological examination, on the potential and critical issues of an increasingly invasive and capillary process.